Methodology of tactical training development among qualified boxers - Kolesnik, I. S.; Gatin, F. A.; Osipov, D. A. (The Russian Journal of Physical Education and Sport, 2016)
Scientific and scientific-methodical literature analysis on the problem of sportsmanship improvement of highly- qualified boxers, progressive pedagogical experience of the leading trainers and specialists in boxing study and summarizing prove the fact that tactical training is an important condition for competitive activity aims realizations. However, in the practice of combatants` sports training main attention is paid to technical readiness increase, at the same time, the skills of tactical techniques use are realized occasionally. Material. The article offers a prospective direction of this problem solution by means of the methodology creation of tactical training development of qualified boxers. The article presents the peculiarities of close combat tactics, the specificity of tactical methods depending on the manner of boxing combat. Research methods: scientific and scientific-methodical literature analysis, progressive pedagogical experience summarizing of the leading specialists and trainers in boxing; observations, pedagogical experiment, testing, static handling of the material. Results. The authors created the methodology of tactical training development of qualified 16-18 years-old boxers, the essence of sports combat tactics is revealed; the used means and pedagogical conditions of skills formation of tactical techniques use. The content of the methodology form the systems of special intellectual and motional tasks, directed at creative thinking development as the base for tactical readiness; logical thinking, which provides the succession of the definite motor acts mastering for the skills formation of a tactical combat during a boxing combat. The evaluation criteria of tactical readiness indices are created. Conclusion. The results of pedagogical experiment showed that tactical training is an important structural component, which provides sportsmanship improvement among qualified boxers. The use of the created methodology provided boxers` physical, intellectual and tactical readiness improvement.